From microtubule remodeling to clinical translation: the multifaceted roles of vasohibin-1 in disease modulation - Wei, Keke; Li, Hui; Huang, Huiquan; Ban, Yinyan; Luo, Xiangbin; Zhang, Chaoren; Guo, Jian; Tan, Minghua; Qin, Minzhen (Frontiers in Immunology, 2026)
Vasohibin-1 (VASH-1) is an endothelial protein that serves as a negative feedback regulator of angiogenesis. Through its microtubule carboxypeptidase activity, VASH-1 plays a key role in vascular homeostasis. While previous studies have investigated its involvement in vascular regulation, most have focused on isolated functions or specific disease models, without systematically addressing its multi-dimensional regulatory mechanisms, tissue-specific functional paradoxes, and translational potential. This review provides a comprehensive analysis of VASH-1’s biological characteristics: its expression is induced by pro-angiogenic factors, and it forms a functional complex with SVBP. In pathological contexts, VASH-1 exhibits paradoxical expression patterns—downregulated in neuroendocrine tumors but upregulated in bladder cancer—and demonstrates tissue-specific functions that either inhibit or promote angiogenesis. Clinically, VASH-1 serves both as a diagnostic marker (e.g., serum biomarker and tissue-based prognostic indicator) and a therapeutic target (such as improving renal disease or promoting tumor vascular normalization). This review aims to elucidate the complex physiological and pathological roles of VASH-1, providing a foundation for future precision intervention strategies targeting VASH-1 in disease diagnosis and therapy.